The Effect of Profitability, Firm Size, Asset Structure and Business Risk on Capital Structure in Mining Sector Companies on the Stock Exchange in 2016-2020 - Wenny Anggeresia Ginting; Dedy Chandra; Kelly Halim; Venyta (Journal of Business, Management, & Accounting, 2022)
This study aims to examine the effect, Profitability, Firm Size, Asset Structure, Business Risk on Capital Structure. This research was conducted on mining companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The number of observations is 131 samples. Sampling using non-probability sampling with purpose sampling technique. The analytical technique used in this research is multiple linear regression analysis. This study states that profitability has no effect and is not significant, while the size of the firm has no effect but is significant on the capital structure of mining companies. And the asset structure and business risk have a negative and insignificant effect on the capital structure of mining companies listed on the Indonesia Stock Exchange for the 2016-2020 period.